The High-Temperature Loading Influence on Orthorhombic Ni3Nb DOa δ - Phase Formation and its Effect on Fatigue Lifetime in Alloy 718 - Belan, Juraj; Vasko, Alan; Kucharikova, Lenka; Tillova, Eva; Matvija, Milos (Manufacturing Technology Journal, 2018)
The orthorhombic DOa Ni3Nb delta phase is naturally presented in microstructure of cast or wrought Ni - Cr - Fe base alloy 718. It is a reason of chemical composition heterogeneity. For delta phase formation is a minimum Nb content about 8% needed and temperature above 650°C and higher. A typical place, where delta phase is situated are grain boundaries in alloy 718, where its role is discutable. Some references saying about lowering the mechanical properties when delta phase is segregated at grain boundary. To approve or disprove of this fact, the wrought alloy 718 with ASTM 12 grain size was subjected to high-temperature loading at push - pull fatigue at low cycle and low frequency (LCLF) and obtained results were compared to results from very high cycle and frequency (VHCF) push - pull loading datas obtained in previous experiments done at room temperature. To support results about influence of delta phase formation an observation on light microscopy and SEM was made too. To increase and make easier identification of delta phase, the techniques of polarised light (DIC - Differential Interferential Contrast) and dark-field (DF) observation were used too.
Keywords: High-temperature loading; Delta phase formation; Microstructure analysis; Dark-field optical microscopy; SEM observation